The expression 5 y 2 has exactly two terms
Answer:
Step-by-step explanation:
![y = sin(xy)\\\frac{d}{dx}y=cos(xy)(\frac{d}{dx}(xy))\\ \frac{d}{dx}y = cos(xy)(y + x*\frac{d}{dx}y)\\ write \: \frac{d}{dx}y \: as\:y'\\y' = cos(xy)(y+xy')\\y' = ycos(xy) + xy'cos(xy) \\y'-xy'cos(xy) = ycos(xy)\\y'(1-xcos(xy)) = ycos(xy)\\\\y' = \frac{ycos(xy)}{1-xcos(xy)}](https://tex.z-dn.net/?f=y%20%3D%20sin%28xy%29%5C%5C%5Cfrac%7Bd%7D%7Bdx%7Dy%3Dcos%28xy%29%28%5Cfrac%7Bd%7D%7Bdx%7D%28xy%29%29%5C%5C%20%20%5Cfrac%7Bd%7D%7Bdx%7Dy%20%3D%20cos%28xy%29%28y%20%2B%20x%2A%5Cfrac%7Bd%7D%7Bdx%7Dy%29%5C%5C%20write%20%5C%3A%20%5Cfrac%7Bd%7D%7Bdx%7Dy%20%5C%3A%20as%5C%3Ay%27%5C%5Cy%27%20%3D%20cos%28xy%29%28y%2Bxy%27%29%5C%5Cy%27%20%3D%20ycos%28xy%29%20%2B%20xy%27cos%28xy%29%20%5C%5Cy%27-xy%27cos%28xy%29%20%3D%20ycos%28xy%29%5C%5Cy%27%281-xcos%28xy%29%29%20%3D%20ycos%28xy%29%5C%5C%5C%5Cy%27%20%3D%20%5Cfrac%7Bycos%28xy%29%7D%7B1-xcos%28xy%29%7D)
Answer:
k < -5
Step-by-step explanation:
5(k+4)<–5
Divide each side by 5
5/5(k+4)<–5/5
k+4 < -1
Subtract 4 from each side
k+4-4 < -1-4
k < -5
Answer:
Quotient of a number and 3 = x/3
Ten less the quotient of a number and 3 will equal 6
So...
10 - x/3 = 6
+ x/3 +x/3
10 = x/3 +6
-6 - 6
3 × 4=(x/3) × 3
12 = x
Your anwser is quit school ):73